Answer: x = 1
Step-by-step explanation:
Simplifying
-4(-6x + 3) = 12
Reorder the terms:
-4(3 + -6x) = 12
(3 * -4 + -6x * -4) = 12
(-12 + 24x) = 12
Solving
-12 + 24x = 12
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '12' to each side of the equation.
-12 + 12 + 24x = 12 + 12
Combine like terms: -12 + 12 = 0
0 + 24x = 12 + 12
24x = 12 + 12
Combine like terms: 12 + 12 = 24
24x = 24
Divide each side by '24'.
x = 1
Simplifying
x = 1
171 minutes
Explanation:
6 is the initial cost, .08 is the cost per minute and 19.68 is the total, set up an equation that looks like this: (x is the unknown variable)
6+.08x=19.68
19.68-6=13.68
.08x=13.68
.08x/.08=x
13.68/.08=171
x=171
Answer:
60
Step-by-step explanation:
y = k/x ( as y is inversely proportional to x)
yx = k
--> k = yx
k = (6)(10)
k = 60
Enjoy it. I hope it will help you.